Evaluating User Experience and Usability of the USEPT Website Using User Experience Questionnaire and System Usability Scale Method - Olivia, Fanny; Ibrahim, Ali (Journal of Information System and Informatics, 2024)
In recent years, assessing the quality of the Sriwijaya University English Proficiency Test (USEPT) website and its user experience has become increasingly important due to the globalization of higher education and the need for students to develop international communication skills. This study aims to evaluate the UX and usability of the USEPT website by using the User Experience Questionnaire (UEQ) and System Usability Scale (SUS) to provide a comprehensive analysis. The results showed that all aspects of the UEQ scored with an average value ranging from -0.88 to 0.48 making it in the “bad” category especially on attractiveness, stimulation and novelty. While the average SUS score is 50 which categorizes usability at the “Not Acceptable” level, with a grade of “F” and adjective rating at the “poor” level. These findings illustrate the poor functionality of the website due to unsatisfactory user experience, thus requiring holistic improvements across all dimensions of UEQ. Recommendations for improvement include optimizing website navigation, increasing visual appeal by creating an attractive design, integrating interactive features to increase user engagement and satisfaction. This research makes a positive contribution to the development of the USEPT website in user satisfaction and can be a reference for website evaluation.